MODEL SISTEM INFORMASI PROTEKSI SERTA PENGASUTAN DAN PENGHENTIAN MOTOR INDUKSI TIGA FASE DENGAN MENGUNAKAN SMS - Adriani Adriani (Fakultas Teknik Universitas Muhammadiyah Makassar, 2020)
As well as the Protection of Information System Models Starting And Penhentian Mi3f By Using Sms. PLC (programmable logic control) is a device (equipment) that is used to replace the sequential relay circuits to control the machine. The research method ology used in the preparation of this final project is besifat experimental study using SMS as a media object to detect an error in an induction motor. The protection of information systems using the instrument for the identification of disorders includes two types: overcurrent relays and current sensors for detecting large flows entering and phase detection in case of failure.